Strategi Pembelajaran Lembaga Pendidikan Pesantren Dalam Mengahadapi Era Digitalisasi: (Studi Kasus di Pondok Pesantren Minhajut Thullab Jombang) - A. Syafi' AS.; Ainun Najib (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2022)
This study aims to examine the learning strategies of Islamic boarding schools in facing the digitalization era at the Minhajut Thullab Jombang Islamic Boarding School. This type of research is descriptive qualitative with data collection techniques through observation, interviews and documentation. While the data analysis techniques use data reduction, data display, and drawing conclusions or data verification. The results of this study indicate that the Education Learning Strategy at the Minhajut Thullab Islamic Boarding School in facing the Digitalization Era, namely First, strengthening the basic values of Islamic education. Second, strengthening human resources at the Minhajut Thullab Islamic Boarding School, such as the ability to think critically, be innovative, creative and have good communication skills, be able to collaborate and have self-confidence. Third, improving infrastructure (facilities) in accordance with technological developments. Fourth, the development of an appropriate pesantren curriculum, in accordance with the times.